Association of Decayed, Missing, Filled Teeth Score With the Risk for Buccal Mucosa Cancer, Stratified on Tobacco and Alcohol Use: A Multicenter Case-Control Study From India - Grace Sarah George; Arjun Singh; Romi Moirangthem; Aniket Patil; Gayathri B. Pullat; Sakshi Sagare; Manigreeva Krishnatreya; Aseem Mishra; Rahul Sonwane; Bayan Hosseini; Anil Chaturvedi; Pankaj Chaturvedi; et al. (JCO Global Oncology, 2025)
PURPOSEBuccal mucosa cancer (BMC), the most prevalent oral cancer (OC) site, is a multifactorial disease. With relatively high prevalence of periodontal diseases because of poor oral hygiene practices, oral health indicators remain an area of exploration in the Indian context for its association with BMC.METHODSA total of 1,673 histologically confirmed cases and 1,601 frequency-matched controls from a hospital-based, multicenter case-control study was analyzed for the risk of BMC because of the oral hygiene indicators—denture use, number of decayed, missing, and filled teeth, and the Decayed, Missing, Filled Teeth (DMFT) score. Logistic regression models, adjusted for potential confounders like age, sex, rural-urban status, education, and tobacco and alcohol use (duration and frequency), were used to estimate odds ratios (ORs) and 95% CI. Analysis was further stratified on tobacco chewing and smoking.RESULTSWe obtained an increased risk of decayed (OR>2 decayed teeth, 1.53; 95% CI, 1.09 to 2.16), missing teeth (OR>2 missing teeth, 2.59; 95% CI, 1.99 to 3.37), and high DMFT scores (OR>3 DMFT score, 2.07; 95% CI, 1.62 to 2.66). Similar results were observed on the stratified analysis. Protective effect was observed for teeth filling (OR>2 teeth-fillings, 0.59; 95% CI, 0.34 to 1.03) and denture use (ORever versus never used dentures, 0.63; 95% CI, 0.47 to 0.85).CONCLUSIONOur findings suggest that DMFT score is associated with the risk of BMC and should be included in national oral health programs for prevention of OCs, along with other indicators of oral hygiene.